Escrita acadêmica em contexto colaborativo online: a prática da resenha em ambiente wiki - Bento, Franciclé Fortaleza (2019)
The present study analyzes the academic literacy practices noticed in the collaborative writing of academic reviews on wiki platform. The theoretical framework of this research comprises English for Academic Purposes (GILLET, 2000; FLOWERDEW; PEACOCK, 2001; HYLAND, 2006) and Computer-Supported Collaborative Writing (ROBERTS, 2005; STAHL; KOSCHMANN; SUTHERS, 2014) approaches; academic writing (HYLAND, 2009; CARLINO, 2017); the review genre (MOTTA-ROTH, 1995a; HYLAND, 2004; MOTTA-ROTH; HENDGES, 2010; ARAÚJO et al., 2018); wiki collaborative writing (CUNNINGHAM, 2008; BENTO, 2011; LANKSHEAR; KNOBEL, 2011); voices in text construction (SHARPLES et al., 1993; HYLAND, 2008; NELSON; CASTELLÓ, 2012) and the academic literacies (LEA; STREET, 1998; KIILI; MÄKINEN; COIRO, 2013). It is an online action research carried out with 17 undergraduate students in English major at Universidade Estadual Vale do Acaraú (UVA), located in Sobral-CE. The scenery of the research was a wiki project for academic reviews collaborative writing, elaborated from the combination of the mentioned approaches and set on the PBworks platform. The project, divided into three modules, provided the apprehension of the review genre, the collaborative writing of this genre and the participants' self-assessment of the literacies needed and summoned for this experience. Therefore, 19 collaborative reviews and the entire process of carrying out this experience were analyzed. The results indicate that reviews elaborated under these conditions are characterized as a reelaborated genre (ARAÚJO, 2016), with new rhetorical movements, some marked in the text itself (citing excerpts of the work and referencing through links) and others marked in the text extension, related to the stages of the writing process (negotiating collaborative writing, deciding collaborative writing, promising collaboration, informing collaboration, encouraging collaboration, and appreciating the review), called floating rhetorical movements. Collaborative authorship shows a close writer-reader relationship, highlights the roles of the writer, the editor, and the evaluator of the reviewed work, and occurs through the use of pronouns that denote engagement with the reader, marked in the text itself, and the collective voice in writing, mainly through sequential work recorded in text editions. The literacies perceived in this experience corroborate the integration of academic literacies (disciplinary literacies, argumentative literacies, digital literacies, collaborative literacies and innovative literacies) and specifically call mobile literacy, part of digital literacies, by using Whatsapp application (auxiliary tool) and critical literacy to constitute the framework of academic literacies.